Magnetic and magnetostrictive properties of aluminium substituted cobalt ferrite synthesized by citrate-gel method - Anantharamaiah, P. N.; Joy, P. A. (Journal Of Materials Science, 2015)
Structural, magnetic and magnetostrictive properties of sintered aluminium-substituted cobalt ferrite, CoAlxFe2-xO4 (x = 0.0, 0.1, 0.20, 0.30), derived from nanosized powders synthesized by a citrate-gel method, have been investigated. The sample with x = 0.1 is found to exhibit higher maximum magnetostriction strain at relatively lower magnetic fields (230 ppm at 286 kA/m) than that obtained for the unsubstituted cobalt ferrite (217 ppm, at 446 kA/m). All the Al-substituted compositions show larger strain sensitivity (d lambda/dH) at low magnetic fields compared to that for the unsubstituted cobalt ferrite. The variation of the magnetostriction coefficient as well as the strain sensitivity with Al content is likely to be due to the changes in the cation distribution in the tetrahedral and octahedral sites of the spinel lattice along with the associated changes in the magnetocrystalline anisotropy. The magnetostriction coefficient of x = 0.1 could be further enhanced to 306 ppm (at 220 kA/m) after a magnetic field annealing at 300 degrees C. A very high strain sensitivity of 4.5 x 10(-9) m/A is obtained for the magnetically annealed sample, larger than that reported for any substituted cobalt ferrite samples. The combination of high magnetostriction coefficient and strain sensitivity is suitable for device applications.

Magnetically tunable liquid dielectric with giant dielectric permittivity based on core-shell superparamagnetic iron oxide - Vinayasree, S.; Nitha, T. S.; Tiwary, C. S.; Ajayan, P. M.; Joy, P. A.; Anantharaman, M. R. (Nanotechnology, 2018)
A liquid dielectric based on a core-shell architecture having a superparamagnetic iron oxide core and a shell of silicon dioxide was synthesized. The frequency dependence of dielectric properties was evaluated for different concentrations of iron oxide. The dependence of magnetic field on the dielectric properties was also studied. Aqueous ferrofluid exhibited a giant dielectric constant of 6.4 x 10(5) at 0.1 MHz at a concentration of 0.2 vol% and the loss tangent was 3. The large rise in dielectric constant at room temperature is modelled and explained using percolation theory and Maxwell-Wagner-Sillars type polarization. The ferrofluid is presumed to consist of nanocapacitor networks which are wired in series along the lateral direction and parallel along longitudinal direction. On the application of an external magnetic field, the chain formation and its alignment results in the variation of dielectric permittivity.

Magnetic parameters of SrFe12O19 sintered from a mixture of nanocrystalline and micron-sized powders - Shashanka, H. M.; Anantharamaiah, P. N.; Joy, P. A. (Ceramics International, 2019)
Obtaining higher magnetic parameters is essential for high-power sintered strontium ferrite (SrFe12O19) for various applications. A novel approach has been made to improve the magnetic parameters of sintered strontium ferrite by making self-composites from nano and micron-sized powders. Powders with two different weight ratios (50 wt% nano:50 wt% micron and 75 wt% nano:25 wt% micron) were mixed together, compacted and sintered at 1200 degrees C for 1 h. For a self-composite of 75 wt% nano and 25 wt% micron-sized powders, coercivity (H-c) of 3076 Oe has been obtained, larger than the values for the sintered compacts from the component powders. The present study suggests that the magnetic parameters of sintered SrFe12O19 can be improved by making self-composite comprising of nanocrystalline and micron-sized powders.
Keywords: Ceramics; Magnetic materials; microstructures; Self-composites; strontium ferrite

Magnetic properties of sintered CoFe2O4-BaTiO3 particulate magnetoelectric composites - Mohan, S.; Joy, P. A. (Ceramics International, 2019)
The magnetic properties of sintered particulate magnetoelectric CoFe2O4 - BaTiO3 composites have been studied. The particulate composites are sintered in the temperature range 1000-1300 degrees C, for a short duration of 10 min. The magnetic transition temperature (T-c) of CoFe2O4 is found to decrease with increasing the sintering temperature and sintering time, as well as on increasing the BaTiO3 content in the composites. Similarly, a reduced saturation magnetization at room temperature, compared to that expected for the CoFe2O4 content, is also observed. Powder X-ray diffraction studies showed the presence of the impurity phase related to the hexagonal ferrite BaFe12O19 in all the composites. Ba2Fe2Ti4O13 is observed as a second impurity phase in the BaTiO3 - rich composites. The present studies suggest that the composition of the piezomagnetic (CoFe2O4) phase in the CoFe2O4 - BaTiO3 magnetoelectric composite is affected during the sintering process.
Keywords: composites; magnetic properties; Sintering